We take it from here:
y^2 + yz = a^2 -az
Move all the z on one side and the rest on the other.
yz + az = a^2 - y^2
z(y + a) = a^2 - y^2
Divide by (y+a);
Hi I'm a tad vexed by this problem
y(y+z) = a(a-z)
I'm trying to rearange it in terms of z.
I thought I should first multiply out the brackets
y^2 + yz = a^2 -az (where ^2 is squared)
Then take the y^2 away
yz = a^2-y^2-az
Divide by y
z= (a^2 - y^2 - az)y
now how do I get rid of z frm the right side or am I aproaching this wrong, another way I tried was taking the whole right side from the left to make a kind of quadratic equation.
Thanks in advance